2020
DOI: 10.2196/14410
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients Using Different Patient Portal Functions and the Impact on Primary Care Service Utilization and Appointment Adherence: Retrospective Observational Study

Abstract: Background Patient portals are now widely available and increasingly adopted by patients and providers. Despite the growing research interest in patient portal adoption, there is a lack of follow-up studies describing the following: whether patients use portals actively; how frequently they use distinct portal functions; and, consequently, what the effects of using them are, the understanding of which is paramount to maximizing the potential of patient portals to enhance care delivery. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…The health system perspective was explored by 15 peer-reviewed [ 45 , 48 , 49 , 59 , 65 , 69 - 71 , 128 - 134 ] and 3 gray literature [ 106 , 109 , 135 ] studies, which focused on the impact of patient portals on the potential for reducing costs. The studies varied in data collection approaches (prospective observational, n=4; retrospective observational, n=9; survey methods, n=2; and mixed methods, n=3), and the evaluated portal components (portal in general, n=11; viewing laboratory results, n=1; OpenNotes, n=1; secure messaging, n=4; appointments, n=2; and care plan, n=1).…”
Section: Resultsmentioning
confidence: 99%
“…The health system perspective was explored by 15 peer-reviewed [ 45 , 48 , 49 , 59 , 65 , 69 - 71 , 128 - 134 ] and 3 gray literature [ 106 , 109 , 135 ] studies, which focused on the impact of patient portals on the potential for reducing costs. The studies varied in data collection approaches (prospective observational, n=4; retrospective observational, n=9; survey methods, n=2; and mixed methods, n=3), and the evaluated portal components (portal in general, n=11; viewing laboratory results, n=1; OpenNotes, n=1; secure messaging, n=4; appointments, n=2; and care plan, n=1).…”
Section: Resultsmentioning
confidence: 99%
“…A recent survey study of a patient portal with access to health care records, test results, e-messaging, and appointment booking reported that patients believed portal use helped them “avoid a clinic visit” [ 39 ]. Few studies in the literature also examined the association between patient portal use and missing medical appointments [ 39 , 40 ], which was not examined in any of the studies included in this review. The health care utilization outcomes associated with patient portal use may need further investigation as the number of studies examining these associations is limited.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is some evidence that increased frequency of patient portal or patient portal functionality use could be associated with increased benefits, suggesting a dose-response relationship. Patient portal adoption does not indicate continuous use [ 40 ]. Since differences in the frequency of use may lead to inconsistencies in benefits acquired from the patient portal, studies need to account for the frequency of patient portal use as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…bDetailed information on the conducted focus groups and the participating users can be found in separate publications. ( 30,31 )…”
Section: Lessons Learned From Working With Action Sheetsmentioning
confidence: 99%
“…This might affect the uptake of newly developed solutions into care delivery because they cannot become embedded into care coordination and workflow design. 30…”
Section: Introductionmentioning
confidence: 99%